Prediksi Profil Farmakokinetik dan Toksisitas Senyawa Aktif Ekstrak Daun Kratom (Mitragyna speciosa) Secara In Silico Menggunakan pkCSM dan SwissADME - anjas, Anjas Wilapangga; Nia marlina Kurnia; Mokhamad Mahroji; Arif Hidayat (The Journal Of Pharmacy, 2025)
The kratom plant (Mitragyna speciosa) has several beneficial pharmacological effects in humans. The pharmacokinetic profiles of secondary metabolites from kratom leaf extract were examined. The aim of this study was to predict the pharmacokinetic and toxicity profiles of active compounds from kratom leaf extract (Mitragyna speciosa) in silico using pkCSM and SwissADME tools. The five main compounds studied were mitragynine, 7-hydroxymitragynine, paynantheine, speciogynine, and speciociliatine. Pharmacokinetic predictions showed that all compounds had good oral absorption profiles and high blood-brain barrier (BBB) ​​penetration, consistent with their pharmacological effects on the central nervous system. However, mitragynine and 7-hydroxymitragynine were predicted to have strong interactions with cytochrome P450 enzymes, particularly CYP3A4 and CYP2D6, indicating potential serious drug-drug interactions. In terms of toxicity, mitragynine is predicted to have mild hepatotoxicity and low genotoxicity. Meanwhile, 7-hydroxymitragynine exhibits a higher toxicity risk profile due to its potent opioid interactions. Overall, these in silico data provide important insights into the potential risks and benefits of kratom use. These results provide a strong foundation for further experimental and clinical studies to validate these predictions and develop guidelines for safe and responsible use.